Effect of graphene oxide on permeability of cement materials: An experimental and theoretical perspective. (September 2021) - Zeng, Hongyan; Lai, Yuanming; Qu, Shen; Yu, Fan
Abstract: In this paper, two kinds of graphene oxide (GO) nanosheets are adopted as additives to reduce the permeability of cement mortars. The structural characteristics of the two GO-modified mortars are compared with a reference sample based on ultrasonic and microscopic analyses. The test results show that 0.06 wt% GO-1 (aspect ratio is 50000) and GO-2 (aspect ratio is 5000) reduce relative permeability coefficient by 80.2% and 41.0%, respectively. Moreover, nanosheets, especially with large aspect ratio, refine capillary pores, regularize hydrated crystals morphology and inhibit microcracks remarkably. To explore the mechanism, a permeability-tortuosity model with considerations of dosage, aspect ratio and arrangement of nanosheets is proposed and validated against the experimental data. For predicting the evolution of structural parameters, theoretical correlations among ultrasonic pulse velocity, porosity and permeability are conducted. It implies that ultrasonic pulse velocity in saturated GO-cement mortar is more sensitive to the change of porosity than that in dry sample when the porosity is smaller than 17%. The proposed model highlights that nanosheets with relatively larger aspect ratio are more helpful for reducing permeability. For case with the application of 0.06 wt% dosage and normal arrangement, the relative permeability ratio is reduced by 80.6% if aspect ratio is increased by 10 times. Highlights: GO nanosheets can refine pores and regulate the morphologies of hydrated crystals. GO with larger aspect ratio are more helpful for impermeability improvement. The proposed model considers the effects of nano dosage, aspect ratio and arrangement. Correlations are built among permeability, porosity and ultrasonic pulse velocity.